HUBUNGAN PENGETAHUAN DAN MOTIVASI BIDAN PRAKTIK SWASTA TERHADAP PELAKSANAAN PIJAT BAYI DI WILAYAH PUSKESMAS KECAMATAN GADING CEMPAKA TAHUN 2011 - Librayani, Shintiya (JURNAL MEDIA KESEHATAN, 2012)
Incidence of low birth weight in Bengkulu City has increased from 7,86% in 2009 to 11.50% in 2010. One effort to increase the stimulation of growth and development in LBW infants is infant massage.The factors that influence it are knowledge and motivation. The perpose of this study was to determine the relationship of knowledge and motivation of midwives in private practice in the implementasi of inflant massage. This study uses an observational design with a descriptive cross sectional approach, total sampling from 59 BPS. Retrievel of data using the primary data through questionnaires. Analyzed by univariate and bivariate chi squer. The results obtained that almost half of respondents did not perfort inflant massage. There was a significant association between knowledge of midwives in private practice with the implementation of inflant massage (p=0.00) and there was a significant association between the motivation of BPS with the implementasi of inflant massage (p= 0.009). the conclusion from the result of this study is there is a significant relationship between knowledge and motivation of midwives in private practice to the implementation of inflant massage.